Fraud Detection in Government Sector - An Analysis on Money Laundering and Bribery - Parampreet Singh Kochar, Shefali Saluja, (International Journal of Advanced Science and Technology, 2020)
The administration and management are responsible to a large extent for ensuring the prevention and detection of fraud in an organisation. It is utmost imperative for the Government sector companies and related organizations to set an appropriate tone at the top by setting personal examples by the top leadership itself, one that is reflective of their commitment towards honest behavior and ethical practices in public and private life. In study we have put an effort to study mechanism of money laundering & forms of bribery. A qualitative analysis was performed with depth literature review based on secondary data available. The study is divided in two phases: 1. Mechanism of Money Laundering and forms of Bribery in Government sector services. 2. Suggesting preventive tools for detection of wrongful practices in the Government sector services. The findings suggest the certain control weaknesses that contribute to fraud include key deficiencies in internal financial controls and managerial oversight, overriding existing controls, poor tone at the higher management level, and lack of competent personnel which can be dealt with some early detection techniques which are discussed in the study. The study would make contribution to Government sector in using this as a manual for training purposes.